Electric field response of molecular reactivity descriptors: a case study - Kar, Rahul; Pal, Sourav (Theoretical Chemistry Accounts, 2008)
In the present article, we study the influence of external electric field on the density-based global and local reactivity descriptors using examples of some planar nonlinear polyatomic molecules with C-2V point group symmetry. The study mainly involves the application of weak electric field in a direction along the principal axis and along its perpendicular direction. We also discuss the strength of the electric field studied in this work in terms of the strength of the molecular interaction. The work is expected to throw light on the effect of interactions within the above range on reactivity descriptors. Results are presented for a few prototype molecules.
Keywords: electric field; molecular interaction; planar nonlinear polyatomic molecules; Reactivity descriptors